2021
DOI: 10.3390/w13101329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Aerobic Denitrifying Bacterium Pseudomonas furukawaii ZS1 on Microbiota Compositions in Grass Carp Culture Water

Abstract: Background: Although functional bacteria are widely used in aquaculture water treatment, whether they affect the indigenous microbiota and whether the impact is persistent remain unclear. Therefore, we aimed to explore the denitrification effect of Pseudomonas furukawaii ZS1 isolated from a grass carp culture pond in nitrogen-rich aquaculture water, and determine whether its effect on the microbiota structure of the aquaculture water was persistent. Methods: Three each of treatment and control groups were set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although high-throughput sequencing of 16S rRNA gene has been widely used to analyze microbiota composition in various environments ( Wu et al, 2017 ; Gong et al, 2021 ), it is difficult to distinguish microorganisms into species or strain level, which hinders a more detailed analysis of the function of gut microbes at species or strain level. Additionally, it is important to further exploit the gut microbiota-derived metabolites of berberine through metabonomics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although high-throughput sequencing of 16S rRNA gene has been widely used to analyze microbiota composition in various environments ( Wu et al, 2017 ; Gong et al, 2021 ), it is difficult to distinguish microorganisms into species or strain level, which hinders a more detailed analysis of the function of gut microbes at species or strain level. Additionally, it is important to further exploit the gut microbiota-derived metabolites of berberine through metabonomics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…If the WQI is concerned about its indicative effect on aquatic vertebrates, it is recommended to use aquatic vertebrate communities as biological community information. Another issue should be clarified is that we had adopted the DNA high-throughput sequencing technology of 16 S rRNA gene to analyze the bacterioplankton community composition in this study, mainly because this method is widely used to analyze the composition of bacterioplankton community (such as [ 1 , [42] , [43] , [44] , [45] ]. However, this does not mean that other analysis methods of plankton community, such as morphological identification [ 20 , 46 , 47 ], are not applicable to the calculation of WQI b and WQI minb that described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For early life stages of cultivated fish, an appropriate administration option may be to add probiotics directly to water containing animal larva and combine this mixture with the use of enriched live feed [78][79][80]. In addition to the beneficial digestive and health effects of probiotics as feed supplements [81,82], adding probiotics to fishpond water can also be beneficial, and these benefits may include improvements in water quality, which is a critical parameter for growth, feed conversion, and farmed fish welfare [83][84][85][86]. Fish excrete NH 4 -N and N compounds in fishponds, and denitrification bacteria can convert these compounds to nitrites and nitrates.…”
Section: Probiotics Can Improve Water Quality Of Freshwater Fishponds and Help Reduce The Environmental Impact Of Freshwater Fish Farmsmentioning
confidence: 99%
“…Probiotic microorganisms have been shown to improve the quality of water in a variety of ways. Heterotrophic bacteria that require both organic and inorganic sources of carbon for growth play a critical role in the breakdown of organic matter and the generation of particulate food items from dissolved organics [83]. Some evidence can be found that suggests that probiotics in freshwater aquaculture ponds or tanks, including recirculated freshwater aquaculture systems, have the potential to reduce toxic levels of NH 3 and P [6][7][8].…”
Section: Probiotics Can Improve Water Quality Of Freshwater Fishponds and Help Reduce The Environmental Impact Of Freshwater Fish Farmsmentioning
confidence: 99%